THE UTILIZATION OF BANANA CORE-STEM WASTE (MUSA X PARADISIACA) FOR HALAL PROTEASE PRODUCTION BY THREE-PHASE PARTITIONING PURIFICATION AND ITS POTENTIAL AS A MILK-CLOTTING ENZYME - Muharrifani, Yefinadya
The critical point for halal enzymes is very dependent on the source of enzyme production. Sources of enzymes that can be ascertained to be halal come from plants. Proteases are needed in various industries, one of which is the milk processing industry because their function is to break down proteins into oligopeptides and amino acids. They can be found in various parts of plants such as roots, fruit, stems, skin, and latex. However, many plant parts have not been reported for proteases, including the core of banana stems which are generally cut down after harvest and become waste. Therefore, this research aims to investigate the use of banana core-stem waste as a source of halal protease and its potential as a milk-clotting enzyme. By extracting, purifying, characterizing, and determining the ratio of milk-clotting activity to protease activity (MCA/PA) from banana core-stem waste protease. Crude extract of banana core-stem waste protease (EKP) obtained through extraction using a pH 8.0 buffer solution was chosen in this study. The total protein content and specific protease activity of EKP were found to be 16.7 mg and 0.19 U/mg, respectively. Electrophoretic analysis using SDS-PAGE on EKP showed a band with an estimated protease molecular weight of ~30 kDa. Purification of EKP using the Three-phase Partitioning (TPP) method was carried out under optimum conditions of ammonium sulfate with a saturation level of 50% (w/v), a mixture pH of 6.0, and a ratio of EKP: t-butanol, 1.0:1.25. The interface fraction (FAM) resulting from purification using the TPP system showed a specific protease activity of 0.66 U/mg with 3.59-fold purification and a recovery of protease activity of 187.5%. FAM can function actively in the pH range 4.0–7.0 and temperature 30–60°C, with optimum pH and temperature respectively at pH 6.0 and temperature 40°C. Furthermore, the MCA/PA ratio of FAM was obtained at 60. This research shows that banana core-stem waste can be used as a source of halal protease and the protease has the potential to be used as a milk coagulating enzyme in cheese production.